Education in Defence of Biodiversity. Will the Ecological and Ethical Footprint Counteract Environmental Changes? - Fiut, Ignacy S.; Urbaniak, Marcin (Problemy Ekorozwoju, 2019)
At the turn of the 20th and 21st centuries, we collectively experienced, and still do, a new kind of border situation – a global environmental disaster. It connects with a newly recognised form of destruction, outside the sphere of biodiversity, which has been called solastalgia. The main source of both solastalgia and irreversible devastation of the biosphere seems to be the attitude of extractivism, that has been lasting steadily for last few centuries. Thee is hope that adequately selected teaching methods of the ecological footprint can effectively raise the sensitivity, empathy and environmental awareness of older and younger generations of consumers. A rescue for biodiversity seems to be biocentric education – perhaps ethical footprint, as an offshoot of ecological footprint, is able to transform Homo rapiens into Homo sapiens again.